2015
DOI: 10.1021/acs.jpcc.5b08306
|View full text |Cite
|
Sign up to set email alerts
|

Current Transport Properties of CuS/Sn:In2O3 versus CuS/SnO2 Nanowires and Negative Differential Resistance in Quantum Dot Sensitized Solar Cells

Abstract: The structural, optical, and electrical transport properties of nanowires obtained by the deposition of Cu over Sn doped In2O3 and SnO2 nanowires followed by processing under H2S between 100 and 500 °C have been investigated for their use in quantum dot sensitized solar cells. We find that the CuS/Sn:In2O3 nanowires obtained between 100 and 200 °C consist of hexagonal CuS and cubic In2O3 but higher temperatures lead to the formation of Cu0.23In2.59S4 nanowires. Moreover, we observed the existence of SnO2 quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…[294] Copper chalcogenide NCs were also used as high conductive electrodes and in solar cells to improve the charge transport. [138,138,[295][296][297][298][299][300][301][302][303] In a recent work, a layer of CuS NCs was used as an inorganic hole-selective layer in inverted planar perovskite solar cells. [304] In the inverted device usually two planar charge transport layers selectively pass electrons and holes created in the perovskite light- Matsui et al [308] showed that the three dimensional assembly of surface-modified ITO NCs leads to plasmon coupling induced high reflectance performance in the near-and mid-IR range due to interparticle plasmon coupling on large-size flexible substrates.…”
Section: Near Field Enhancing Spectroscopy With Nir Plasmonic Semiconmentioning
confidence: 99%
“…[294] Copper chalcogenide NCs were also used as high conductive electrodes and in solar cells to improve the charge transport. [138,138,[295][296][297][298][299][300][301][302][303] In a recent work, a layer of CuS NCs was used as an inorganic hole-selective layer in inverted planar perovskite solar cells. [304] In the inverted device usually two planar charge transport layers selectively pass electrons and holes created in the perovskite light- Matsui et al [308] showed that the three dimensional assembly of surface-modified ITO NCs leads to plasmon coupling induced high reflectance performance in the near-and mid-IR range due to interparticle plasmon coupling on large-size flexible substrates.…”
Section: Near Field Enhancing Spectroscopy With Nir Plasmonic Semiconmentioning
confidence: 99%
“…55 Hence, in principle, the Sb:SnO 2 NWs described here may be processed into devices capable of light emission but also NWSCs. 56,57 To the best of our knowledge no one has previously used ordered networks of Sn:In 2 O 3 or Sb:SnO 2 NWs to make NWSCs despite the fact that Battaglia et al 58 has showed that periodic photonic nanostructures outperform their random counterparts in trapping light in solar cells. It is desirable then to use these highly conductive, ordered networks, of Sb:SnO 2 NWs in order to improve the performance of all-solid state NWSCs.…”
Section: Optical Properties Of Sb:sno 2 Nws On M- R-and A-al 2 Omentioning
confidence: 99%
“…Consequently, the junction area formed by the deposition of a barrier, absorber, and p-type layer over the ordered network of Sn:In 2 O 3 TCO NWs is expected to be considerably larger compared to that of a planar device, which in turn is expected to lead to a significant increase in the short circuit current. In the past, Sn:In 2 O 3 NWs have been used mainly for the fabrication of dye-sensitized solar cells, but they were not grown in an epitaxial fashion and as such were not ordered. , To the best of our knowledge, no one has previously used ordered networks of Sn:In 2 O 3 NWs in NWSCs despite the fact that periodic photonic nanostructures have been shown to outperform their random counterparts in trapping light in solar cells . Although other metal oxide (MO) NWs such as ZnO NWs have been used for the fabrication of all-solid-state NWSCs, they are not as highly conductive as the Sn:In 2 O 3 NWs described here, which in turn limits the short circuit current and performance of NWSCs.…”
Section: Resultsmentioning
confidence: 99%